Effect of Parkia speciosa Hassk Peels Extract on Total Cholesterol Levels of Hypercholesterolemia Rats - Joni Tandi1 , Tien Wahyu Handayani1 , Maria Tandebia1 , Jessica Anastasia Wijaya1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: This research aimed to examine the secondary metabolites in the ethanol extract of Parkiaspeciosa Hassk peels and determine the effect of the P. speciosa Hassk peels on the reduction in totalcholesterol levels of male hypercholesterolemia white rats.Methods: Thirty white male rats were divided into six treatment groups (n=5): Group I: normal control(0.5% CMC Na suspension), Group II: negative control (high cholesterol feed), Group III: positive control(suspension simvastatin), Group IV, V, VI: hypercholesterolemia rat received P. speciosa Hassk shell at doseof 300, 400, and 500 mg/kg BW orally for 14 days. The total cholesterol levels were measured on days 0,14, 28, 35.Results: Quantitative test showed that the ethanol extract of P. speciosa peels contained 0.21% alkaloids(w/w), 8.34% flavonoids (w/w), 4.21% tannins (w/w) and 0.18% saponins (w/w). The ethanol extract of P.speciosa peels at a dose of 300 mg/kg BW was able to reduce total cholesterol levels in hypercholesterolemiawhite mice (52 mg/dL).Conclusion: The ethanol extract of P. speciosa peels can be considered as an effective treatment forhyperlipidemia disease.